BELIBIS POTÈ ROSI’S AS A DHÂLÂNG MASK DANCE OF THE RUKUN PEWARAS IN SUMENEP - Ristiana, Eva Ristiana; Wahyuni Rahayu, Eko (Solah, 2025)
Abstract Rosi is the name of a young man in Sumenep Regency who is engaged in the profession of dancer in the performing art of topèng dhâlâng. As a dancer of the topèng dhâlâng performance, he is able to play various character characters ranging from princess characters, subtle sons, to dashing male characters. Her expertise in portraying all the characters was able to lead her to become a famous topèng dhâlâng dancer and many fans. This study aims to describe Rosi's professionalism as a topèng dhâlâng dancer in the Rukun Pewaras community in Sumenep Regency. The research method uses a qualitative approach with data collection techniques through observation, interviews, and literature studies, and documentation studies. The results of the study show that Rosi in pioneering the profession as a topèng dhâlâng dancer began when Rosi was studying in 2012. With the support of her family, her enthusiasm, her great interest and interest in the performance of topèng dhâlâng made her more steady and diligent in practicing as a dancer in the Topèng Dhâlâng Rukun Pewaras community. Rosi's professionalism as a topèng dhâlâng dancer is shown through the ability to bring various characters, be it the role of a princess, a subtle son character, and a dashing son character overnight. For Rosi, becoming a topèng dhâlâng dancer is a life calling, has a strong dance style, and always maintains the professional code of ethics. As a dance artist, Rosi is also known in the world of Tayub Madura performing arts through her distinctive dance style influenced by the technique and movement pattern of the topèng dhâlâng dance. Through Rosi's profession as a topèng dhâlâng dancer, she can strengthen the existence of the Topèng Dhâlâng Rukun Pewaras community in Sumenep Regency.